A Case Study of Vitamin D Supplementation Therapy and Acute Respiratory Tract Infection - Simanek, Vaclav; Dedeckova, Eva; Topolcan, Ondrej; Kralova, Marketa; Kucera, Radek (In vivo (Athens, Greece), 2024)
BACKGROUND: Low serum concentrations of 25-hydroxyvitamin D correlate with higher susceptibility to acute respiratory tract infections (ARTIs). The case study presented here aims at sheding light on the correlation between vitamin D levels, the vitamin D supplement dose, and the incidence of ARTIs. CASE REPORT: A 23-year-old female patient with a vitamin D insufficiency was able to successfully increase her vitamin D levels from 45.60 nmol/l to 85.91 nmol/l (reference ranges 75-200 nmol/l) through the use of supplements. However, it was surprising to observe a decrease in vitamin D levels even though the patient continued taking supplements. Further examination indicated that the patient was experiencing common symptoms of an acute respiratory tract infection (ARTI). This case highlights the intricate connection between ARTIs and vitamin D intake. CONCLUSION: This case study clearly demonstrates the intricate connection between vitamin D levels, supplement treatment, and ARTIs. The observed decrease in vitamin D levels during the course of supplementation, while the patient was suffering from an ARTI, suggests that respiratory infections may affect vitamin D metabolism.
Keywords: Vitamin D Deficiency; Humans; Vitamins; Respiratory Tract Infections; vitaminy; supplementation; nedostatek vitaminu D; vitamin D deficiency; Female; mladý dospělý; dospělí; [25(OH)D)]; lidé; acute respiratory tract infection; Vitamin D; human immunity; Adult; ženské pohlaví; retrovirus; potravní doplňky; infekce dýchací soustavy; Dietary Supplements; Young Adult; vitamin D